PENGARUH STRES PERAN PADA KEPUASAN KERJA, DAN IMPLIKASINYA TERHADAP INTENSI KELUAR DENGAN VARIABEL AFEK POSITIF SEBAGAI PEMODERASI - Irfandi Buamonabot (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
This study examines the effect of role conflict on job satisfaction , ambiguity on job satisfaction , job satisfaction and intentions out and positive affect moderating on the relationship between job satisfaction and intentions out . The purpose of this study was to determine : ( a) examine the effect of role conflict on job satisfaction , ( b ) examine the effect of role ambiguity on job satisfaction , ( c ) examine the effect of job satisfaction on intentions out , ( d ) examine the influence of positive affect moderating on the relationship between job satisfaction and intentions out .Respondents were collected in this study is that the police have a double post and served in North Maluku Police and his staff . Total of 154 respondents were collected from the survey Data analysis was performed using simple regression and hierarchical regression.The results showed that : (a ) role conflict has a negative effect on job satisfaction , ( b ) role ambiguity has a negative effect on job satisfaction , ( c ) job satisfaction has a negative effect on exit intention , ( d ) positive affect did not moderate the relationship between job satisfaction . Conclusion The results showed that the level of work stress ( role conflict and role ambiguity ) Police are at relatively low levels , high levels of job satisfaction and intentions out lower level , as well as positive affective moderating not as a variable in the relationship between job satisfaction and intentions exit